Prediction of the presence of plantaris tendon through examination of palmaris longus tendon. Is there a link? - Köse, Özkan; Ege, Tolga; Demiralp, Bahtiyar; Sanal, Tuba; Bek, Doğan; Başbozkurt, Mustafa (Sociedad Chilena de Anatomía, 2014)
The purpose of this study was to investigate the relationship between palmaris longus (PL) and plantaris (P) tendons and test the clinical usefulness of symmetry patterns between these tendons in Turkish population. This prospective study comprised a total of 240 adult patients (120 men and 120 women) who were admitted to our outpatient clinic with bilateral knee complaints that required bilateral knee MR examination during two years. Standard test (Schaefer's test, oppose the thumb to the little finger while flexing the wrist) was used to assess the presence of the PL tendon both with inspection and palpation. Knee MRI was used to determine the presence of P muscle belly on both sides. We have analyzed symmetric distribution pattern using Mc-Nemar test. The PL was absent unilaterally in 34 subjects (14.2%), while it was absent bilaterally in 17 subjects (7.1%). The P was absent unilaterally in 51 subjects (21.3%), while it was absent bilaterally in 10 subjects (4.2%). If PL was absent in one hand, the chance of having an ipsilateral P tendon was 70.6%. If PL was present in one hand, the chance of having an ipsilateral P tendon was 87.6%. The Mc-Nemar test for symmetry yielded a p value of 0.841 for ipsilateral PL and P muscles. A clear-cut link between Palmaris longus and plantaris tendons could not be demonstrated in this study. Both muscles show different variations independent from each other.

El propósito de este estudio fue investigar la relación entre los tendones del músculo palmar largo (MPL ) y músculo plantar (MP) y poner a prueba la utilidad clínica de los patrones de simetría entre estos tendones de la población turca. Estudio prospectivo realizado sobre 240 pacientes adultos (120 hombres y 120 mujeres) que ingresaron en la clínica por síntomas de dolor en la rodilla bilateralmente, quienes requerían un examen de RM de rodilla durante dos años. Se utilizó la prueba estándar (prueba de Schaefer, se oponen el pulgar hasta el dedo mínimo, mientras se flexiona la muñeca) para evaluar la presencia del tendón MPL tanto con la inspección y palpación. La RM de la rodilla se utilizó para determinar la presencia de vientre muscular plantar en ambos lados. Se analizó el patrón de distribución simétrica mediante la prueba de McNemar. El tendón del MPL estuvo ausente de manera unilateral en 34 pacientes (14,2%) y bilateralmente en 17 pacientes (7,1%). El tendón del MP estuvo ausente de manera unilateral en 51 pacientes ( 21,3 %) mientras que bilateralmente no estaba en 10 pacientes (4,2%). Si el tendón del MPL estuvo ausente en un lado, la probabilidad de tener un tendón del MP ipsilateral fue del 70,6 %. Si el tendón del MPL estaba presente en un lado, la probabilidad de tener un tendón del MP ipsilateral fue 87,6%. La prueba de McNemar - simetría produjo un valor p de 0,841 para los músculos PL y P ipsilaterales. Una relación directa claro entre los tendones de los músculos PL y P no se pudo demostrar en este estudio. Ambos músculos muestran diferentes variaciones independiente uno del otro.
Predicción de la presencia del tendón del músculo plantar mediante el examen del tendón del músculo palmar largo. ¿hay una relación?
WOS: 000339241600035
Keywords: M. Palmaris Longus; M. Plantaris; Tendon Graft; Prevalence; M. Palmar Largo; M. Plantar; Injerto de Tendón; Prevalenci